Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Jafra Pada Pt Jafra Cosmeticts Indonesia (Studi Kasus Konsumen Konsultan Fortuna Mazka di Kota Jambi) - Bella Hartati (JUMANJI (JURNAL MANAJEMEN JAMBI), 2023)
This research consist of independent variable that is product quality and price, and dependent variable that is purchasing decision. The formulation of the problem how the influence of independent variables to the dependent variable simultaneously and partially. In this study the method used is quantitative descriptive method. The analytical tool used is statistical analysis consisting of multiple linear regression equations, determination coefficients, classical assumption tests, and hypothesis testing. The object in this study was PT JAFRA Cometics Indonesia. Brief histori of JAFRA was founded in 1956 in Malibu, California when Jan and Frank Day gave brith to mission to help women achieve personal freedom by becoming an independent businessman. Based on the results of the study assisted by SPSS 20 software, the regression equation Y = 0.262 + 0.393 + 0.534 + e. Simultaneously the independent variables have a significant effect on the dependent variable which is indicated by fcount> ftabel and partially the product quality variable and price variable have a positive effect on purchasing decisions. R square 84,7% and the rest 15,3% explain other variable outside research model. Conclusion Product quality and price variables have a significant and simultaneous effect on purchasing decision variables and product quality and price variables have a partial positive effect on purchasing decision variables.